PERAN GIRLS NOT BRIDES DALAM MEMINIMALISIR KASUS PERNIKAHAN ANAK / CHILD MARRIAGE DI NIGERIA PERIODE 2016 - 2020 - Sakinatunnafsih, (2021)
This research was conducted on the basis of problems related to child marriage that occurred in Nigeria with the aim of knowing, to find out and explaining the role of Girls Not Brides as an INGO (International Non-Governmental Organization) in handling cases of Child Marriage in Nigeria along with the opportunities and challenges. The research method used in writing this essay is descriptive qualitative which aims to describe and elaborate in general how the case of child marriage in Nigeria is an urgent problem and is very impactful and detrimental to various parties. Through the concept of relations or patterns of relations between INGOs and the state government also with role theory, the role and position of Girls Not Brides as actors in coalition with the Nigerian government can be divine. Data collection techniques are carried out by collecting official document or library research through various relevant literature / article from both print and electronic media. The data that has been collected is analyzed using qualitative data analysis techniques that are filtered and then connected to each other to achieve a pattern of understanding and good conclusions on the role of Girls Not Brides in minimizing child marriage cases in Nigeria for 2016-2020 period. Keyword: Girls Not Brides, Role, Child Marriage, Nigeria